Analysis of Aid Distribution and Mitigation of the Causes of Flood Disasters in Karangnanas Village - Nabila Syifa; Umi Haniati (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study analyzes the distribution of aid and mitigation of the causes of flood disasters in Karangananas Village, Sokaraja District, Banyumas Regency. The purpose of this study is to analyze the extent to which aid provided to flood victims has been distributed and to examine the main causes of flooding in the village. In addition, this study also aims to compile mitigation steps that can be taken to prevent similar disasters in the future. This study uses a qualitative descriptive method with in-depth interviews, direct observation, library studies and through Pusdalops data at the Banyumas Regency BPBD. The factors causing flooding in Karangnanas Village consist of very high rainfall, poor drainage infrastructure, and uncontrolled land conversion. Therefore, preventive measures that can be taken include improving drainage infrastructure, building water storage, improving the management of green open spaces, and increasing public awareness of the importance of preserving the environment.